Pemanfaatan Manajemen Pengetahuan untuk Membantu Persiapan Data pada Proses Data Mining - Yusuf Bayu Wicaksono; Christina Juliane (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
The data mining process always involves a data preparation stage. Based on the experience of IBM data mining practitioners, 40-70% of data mining project time is spent on data preparation. This is because not everyone knows what the content of the available data is, so it will take time just to understand the data itself. The research method used adopts an information systems research framework, by comparing the knowledge base (data mining) with environmental facts (the duration of data preparation). Design/research is made using a knowledge management approach designed for data. Two qualitative and quantitative tables containing data related knowledge are used as an explicit form of data. With this knowledge the data preparation process can be shortened because miners are not mining data from zero knowledge.